How national bioeconomy strategies address governance challenges arising from forest-related trade-offs. Issue 1 (2nd January 2022) - Schulz, Tobias; Lieberherr, Eva; Zabel, Astrid
ABSTRACT: The term 'bioeconomy' stands for an economy that primarily relies on renewable biotic resources and thus supports the vision of a low carbon society. The respective 'bioeconomy strategies' bear high conflict potential as they, sometimes unintentionally, rely on forest-land or wood as a resource, which are already appropriated also in other policies. We first outline the resulting governance challenges in terms of coherence of policy goals, consistency of instruments and the congruence between the two and identify trade-offs between forest ecosystem services that exhibit a high conflict potential regarding the bioeconomy. We then provide a comparative analysis of the extent to which bioeconomy strategies tackle the related governance challenges for two pairs of countries from the temperate (Germany and Switzerland) and the boreal (Sweden and Norway) forest zone. We find that the strategies do not mention conflicts related to wood mobilization. Coherence and consistency tend to be addressed for non-extractive forest utilizations that are perceived as a market opportunity rather than solely a restriction on wood mobilization. The latter seems more common in countries with a multi-functional forestry paradigm. Consequences for the prevailing forest management paradigm, however, are not explored in the strategies and thus policy congruence is neglected.